Meta-analytic reviews of board composition, leadership structure, and financial performance - Dalton, Dan R.; Daily, Catherine M.; Ellstrand, Alan E.; Johnson, Jonathan L. (Strategic Management Journal, 1998)
Careful review of extant research addressing the relationships between board composition, board leadership structure, and firm financial performance demonstrates little consistency in results. In general, neither board composition nor board leadership structure has been consistently linked to firm financial performance. In response to these findings, we provide meta-analyses of 54 empirical studies of board composition (159 samples, n = 40,160) and 31 empirical studies of board leadership structure (69 samples, n = 12,915) and their relationships to firm financial performance. These—and moderator analyses relying on firm size, the nature of the financial performance indicator, and various operationalizations of board composition—provide little evidence of systematic governance structure/financial performance relationships. © 1998 John Wiley & Sons, Ltd.